A Comparative Study of the creatine kinase activity in human seminal fluid and its Relation with fertility - Enam Ahmad Hamza (مجلة التربية والعلم, 2013)
Abstract New approaches need to be pursued towards the assessment of sperm quality using biochemical markers and develop this markers to assess sperm function. The current study included analyzed 52 samples of human's seminal fluid wich classified into three classes: fertile normospermea (control), infertile oligospermea and azospermea. The percentage of dead sperms were obtaind by using eosin die in addition to the use of trypan blue to show the intact acrosome. The results of the study showed that the concentration of sperm in human's seminal fluid samples was (63x106/ml).The results showed ahigher level of creatine kinase CK  activity in human seminal plasma in an infertile oligospermic (113.3±17U/L) and azospermic cases (97.1±11U/L) in comparison to the control normospermic case (48.5±9U/L).